Meningkatkan Pemahaman Siswa Menggunakan Model Game Based Learning pada Pembelajaran IPAS Materi Kedatangan Bangsa-Bangsa Asing ke Indonesia di Kelas VI SD - Lisna Agustin; Aulia Dila Pratiwi; Dian Nurlela; Nurroh Muna Mu’adah; Via Siti Fatimah; Rana Gustian Nugraha (Lembaga Yasin AlSys, 2026)
Learning in the IPAS (Integrated Science and Social Studies) subject on historical topics in elementary schools is often perceived as monotonous by students, resulting in low learning focus, limited classroom participation, and learning outcomes that do not yet meet the Kriteria Ketercapaian Tujuan Pembelajaran (KKTP, Learning Objectives Achievement Criteria). This situation requires teachers to implement learning models that are more innovative, interactive, and aligned with students’ characteristics and learning needs. This study aimed to improve students’ conceptual understanding and learning outcomes through the application of a Game-Based Learning model in the topic “The Arrival of Foreign Nations in Indonesia.” The research employed a Classroom Action Research method implemented over two instructional cycles with 22 sixth-grade students at SDN Nyalindung 1 as the research subjects. Data collection techniques included cognitive tests to measure learning outcomes and observation sheets to assess students’ activity, participation, and engagement during the learning process. The results showed a positive improvement, indicated by an increase in the average student score from 75.00 in Cycle I to 85.00 in Cycle II. In addition to cognitive gains, the implementation of Game-Based Learning also significantly enhanced students’ activeness, enthusiasm, and motivation to learn. Thus, the Game-Based Learning model is effective in improving students’ understanding and learning outcomes in IPAS history learning, although further optimization of classroom management strategies and variation in game activities is still needed to ensure that classical mastery learning is achieved in a maximal and sustainable manner.